Heat impacts on health and productivity: the case of two ready-made garment factories in tropical Bangladesh - Farzana Yeasmin; Aaron J. E. Bach; Jean P. Palutikof; Fahim Tonmoy; Fahmida Tofail; Mahbubur Rahman; Shannon Rutherford (Environmental and Occupational Health Practice)
Objective: The ready-made garment (RMG) sector is pivotal to Bangladesh’s economy, providing export opportunities and employment. To ensure sustained productivity and a thriving workforce, workplace hazards like heat must be acknowledged, assessed and managed. This paper explores heat impacts on health and productivity of production-line workers in two RMG factories of Bangladesh. Methods: Focus group discussions and in-depth interviews were conducted with the workers of two RMG factories in Dhaka in 2022 to identify perceived heat-related health and productivity impacts and explore barriers to workers accessing heat-related medical care. Key informant interviews were conducted with factory officials, onsite health professionals, government officials, the RMG peak body, and non-government organisation professionals with expertise in industry and workplace issues. Results: Workers and health professionals attributed symptoms like headaches, dizziness, fatigue and nausea to heat. Factory health professionals observed changes in cardiovascular strain (eg, altered blood pressure responses) in workers during summer. Other key informants identified higher absenteeism across summer. Heat was identified as an impediment to overall productivity by workers themselves and others working across the sector. Conclusion: This qualitative study identified how heat exposure in indoor work environments of RMG in Bangladesh influences health of workers and how productivity is influenced directly by heat but also indirectly via necessary cooling measures to reduce heat strain that take workers away from the production line. Despite knowledge of access to hydration as an important heat health risk mitigation strategy, quota pressures inherent in these factories restrict the use of this vital measure.